2021
DOI: 10.1101/2021.12.12.472090
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Landscape of Epithelial Mesenchymal Plasticity as an emergent property of coordinated teams in regulatory networks

Abstract: Elucidating the principles of cellular decision-making is of fundamental importance. These decisions are often orchestrated by underlying regulatory networks. While we understand the dynamics of simple network motifs, how do large networks lead to a limited number of phenotypes, despite their complexity, remains largely elusive. Here, we investigate five different networks governing epithelial-mesenchymal plasticity and identified a latent design principles in their topology that limits their phenotypic repert… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 67 publications
1
20
0
Order By: Relevance
“…S2E ), i.e., genes regulating a phenotype are positively correlated with each other and negatively correlated with genes regulating the other phenotype. Such ‘teams’-like interactions have been shown to play a role in regulating phenotype switching and multi-stability in biological systems 41,42 . Transition paths based on the energy landscapes for the two trajectories (de-differentiation and hyperpigmentation) reveal the changes in gene expression as cells transition from one state to another ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S2E ), i.e., genes regulating a phenotype are positively correlated with each other and negatively correlated with genes regulating the other phenotype. Such ‘teams’-like interactions have been shown to play a role in regulating phenotype switching and multi-stability in biological systems 41,42 . Transition paths based on the energy landscapes for the two trajectories (de-differentiation and hyperpigmentation) reveal the changes in gene expression as cells transition from one state to another ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…From both methods, we now have stable steady states as binary strings (0 → Low, 1 → High). We then characterize these steady states into hybrid or “terminal” (referring cumulatively to epithelial and mesenchymal states) based on an EMT score (Hari et al 2021) ( Fig 1C ) and define the ‘hybridness’ of a network as fraction of steady state frequencies that can be classified as hybrid E/M (see details in materials and methods).…”
Section: Resultsmentioning
confidence: 99%
“…Frustrated phenotypes can then be viewed as those resulting from gene expression patterns that may be the outcome of conflicting signals. Recent computational analysis of some EMP networks showed high frustration for hybrid phenotypes compared to the terminal phenotypes (Hari et al 2021). We investigated whether the relationship between frustration and hybridness is maintained across perturbations in these EMP networks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The deeper an attractor (or a Waddington landscape's valley), the more difficult it gets to transition out from that phenotype. Multiple mathematical attempts to construct such landscapes for intracellular transcriptional networks driving E-M plasticity have shown that the "attractors" corresponding to hybrid E/M states are relatively shallow as compared to those corresponding to E and M states (31,32). This salient feature of hybrid E/M cells can help explain their higher plasticity (28)(29)(30).…”
Section: The Composition Of the Population B) Regaining Of Original P...mentioning
confidence: 99%